The Effectiveness of the Online Educational Platform Blackboard in Managing Education Processes At the University Of Hail a Field Study from the Faculty Members' Point Of View (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study aimed to identify the effectiveness of the electronic educational platform Blackboard in managing education operations at the University of Hail.The sample of the study consisted of 12 faculty members at the University of Hail.The interview was used.The qualitative approach was used to suit the study applications.The results of the study concluded that the most used services were primarily raising course plans and teaching content and raising and receiving assignments from students, then this is followed by cloud storage, discussion and dialogue rooms, and e-mail, and in the last comes electronic exams, monitoring grades, and creating virtual classes, blogs, wikis, and groups of students, and opinion polls.The results showed that the facilities are primarily in providing training courses and providing technical support. The difficulties were evident in the weakness of technical support and the lack of training courses.